Translation and cross-cultural adaptation of EAT-26 questionnaire in Urdu - Anam Jamil; Nida Zahid; Momina Imtiaz; Hadia binte Obaid; Asma Muhammad; Aniqa Jamil (MethodsX, 2023)
EAT-26 questionnaire is used globally to screen people for the risk of eating disorders. In addition to this, the EAT-26 is being used in its original English version in research and clinical settings due to unavailability of the Urdu version. Therefore, the aim of this study was to introduce the Urdu version of EAT-26 to clinicians and academicians in Pakistan, interested in the assessment of population at risk of eating disorders. After getting the formal permission for translation by Dr. D. M. Garner, WHO guidelines were followed for the translation and adaptation process. Two independent translators with psychological background worked under the supervision of a lead to produce the definitive version following six steps of translation and adaptation. Cognitive interviews and focused group discussions helped in the assessment process for the understanding level of translated Urdu version. The pre-final version showed comprehension and acceptability during initial pilot testing. • The final translated version of EAT-26 in Urdu will be available on Internet to use. It is expected that the use of EAT-26 will be widespread in Pakistan, aiming at the assessment of eating disorders. • The Urdu version of EAT-26 is finalized, and ready to use by researchers and clinicians in Pakistan.